Retinal detachments in a patient with minimal change nephrotic syndrome: Case report and review of the literature - Ye, Chunjian; Qiu, Miaohua; Zhong, Yu; Chen, Jiejian (Frontiers in Nephrology, 2023)
Background: To report an unusual case of minimal change nephrotic syndrome with sudden bilateral retinal detachment. Case presentation: A 54-year-old woman with nephrotic syndrome was presented with blurred vision in both eyes. Her optical coherence tomography scans revealed the presence of subretinal fluid in the subfovel area.A kidney biopsy confirmed the diagnosis of minimal change disease. Glucocorticoid therapy was quickly started. During remission, her vision is restored and a disappearance of the subretinal fluid on optical coherence tomography was observed. Conclusions: In minimal change nephrotic syndrome cases, fluid accumulation in the retina layer may occur, gravity-induced vitreous traction on the inferior retina may cause retinal detachment.Identifying these abnormalities is essential to avoid diagnosis wandering and therapeutic delay.